Camptotechin loaded sodium casein nanoparticles for targeted drug delivery to multi-drug resistance prostate cancer cells - Ilias, Muhammad Ihsan (2015)
Prostate cancer is the development of cancer cells in the prostate glands of the male reproductive system and the most commonly diagnosed cancer in male, especially in developed western countries (Dasgupta & Kirby, 2011). In Malaysia, prostate cancer is the fourth most common cancer diagnosed in men (Omar & Tamin, 2011 ). The mortality rate of cancer is reduced but therapy and surgery costs are expensive (Yallapu et al., 2014). Chemotherapy is not very effective because it causes undesirable side effects to the normal healthy cells which reduce the quality of life of cancer patients (Sowery, So, & Gleave, 2007). Moreover, after a period, the tumour cell becomes immune to chemotherapeutic drugs leading to multi-drug resistance (MDR).